Europe as a Convergence Engine : Heterogeneity and Investment Opportunities in Emerging Europe - Stojkov, Aleksandar; Zalduendo, Juan (2012)
This paper provides empirical evidence that countries in emerging Europe reaped the benefits of international financial integration over the past 12 years by attracting sizeable foreign capital inflows and accelerating medium-term growth. But the aggregate pattern masks substantial heterogeneity across countries; namely, new European Union member states and the European Union candidate countries are different from the European Union neighborhood. The growth benefits are supported from both a flow and a stock perspective in terms of the link between foreign savings and growth. While foreign savings might in part substitute for national savings, the analysis finds that the channel to high growth in these countries is, primarily, through making possible the pursuit of investment opportunities that would otherwise remain unfunded; in turn, this seems to be intimately linked to the opportunities created by European Union membership. Although this conclusion does not disappear if the outlier observations of the credit boom period that preceded the financial crisis are dropped from the sample, it does suggest that these excesses did not play as positive a role for growth.